PENGARUH MODEL PEMBELAJARAN SCRAMBLE DENGAN MEDIA CAMTASIA TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS VII UPT SMPN 27 MEDAN - Rohani Oppusunggu, Rini; Yuhdi, Achmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of technology in the 21st century requires innovation in Indonesian language learning, especially in writing skills. This study aims to evaluate the effectiveness of the Scramble learning model integrated with Camtasia media on the procedural text writing skills of 7th-grade students at UPT SMPN 27 Medan. The methodology employed was a quantitative experiment using a One-Group Pretest-Posttest Design with a sample of 29 students. Data were collected through essay tests and analyzed using t-test statistics. The results indicated a significant improvement: the pretest average was 49 (poor category), increasing to 66 (good category) in the posttest. Statistical analysis yielded a thitung = 5.57, exceeding ttabel = 2.048 (df=28, α=0.05). These findings confirm that the Scramble model combined with Camtasia media significantly enhances students' ability to organize procedural steps and apply linguistic rules, providing a more interactive and structured learning environment.